Integrated computational and experimental identification of N-[(1H-1,2,4-triazol-3-yl)phenyl]-1-(1H-pyrazolo[3,4-b]pyridin-3-yl)methanamide as a potent and selective TIM-3 inhibitor for NSCLC immunotherapy - Ying, Xinxin; Lou, Yangyong; Wu, Yueming; Hu, Weiwei (Frontiers in Chemistry, 2025)
Non-small cell lung cancer (NSCLC) remains a significant clinical challenge, necessitating exploration of novel therapeutic targets such as TIM-3. In this study, integrated computational and experimental methods were utilized to identify potent TIM-3 inhibitors. Survival analysis revealed a significant correlation between elevated TIM-3 expression and decreased patient survival. Structure-based virtual screening and molecular dynamics simulations identified HIT104310526 (N-[(1H-1,2,4-triazol-3-yl)phenyl]-1-(1H-pyrazolo[3,4-b]pyridin-3-yl)methanamide), a candidate exhibiting superior binding affinity and stable interactions within the TIM-3 binding pocket. MMGBSA binding free energy calculations and metadynamics further confirmed its potent binding. Physicochemical evaluations indicated favorable drug-likeness, although solubility improvement is needed. Experimental validation showed selective cytotoxicity of HIT104310526 toward NSCLC cells (A549; IC50 = 37.74 μM), with negligible toxicity to normal bronchial epithelial cells (BEAS-2). However, potential cardiotoxicity risks were identified. Collectively, HIT104310526 demonstrates substantial promise as a selective TIM-3 inhibitor, warranting further optimization for NSCLC treatment.